(untitled) (Research, Society and Development, 2021)
The objective is to inform about the development of an application to support clinical consultation in sexually transmitted infections. This is a methodological study, of an exploratory, experimental and applied nature, carried out based on the information and communication technology entitled mHealth. The application’s functionalities were designed based on the current regulation for the control of sexually transmitted infections, clinical protocol and therapeutic guidelines for comprehensive care for people with sexually transmitted infections, focusing on key and priority populations, aiming at prevention, early detection, diagnosis, treatment of users and partnerships to break the transmission network. For that, we used the incremental software processing model and its five stages of development called communication, planning, modeling, construction and employment, which finalized result in the delivery of an increment, that is, a functional version of the application. Through React Native and its Javascript library, we are in the construction phase of the technological artifact. Thus, it is expected to contribute to the qualification of professional practice and improvement of the provision of care to users in primary health care services, as well as assisting professionals in clinical decision-making in consultations for sexually infected patients. communicable diseases.